KASBGA XOS ME’YORLARNING PSIXOLOGIK JIXATLARI - Jumaniyozova, N.; Yusupova, Z. (SCIENCE and SOCIETY, 2017)
The activities of government in the development of society are very important. We can prognosticate the positive feature of the psychological climate among people by the spiritual guiding, Kuping the national peculiarities at the same time. The author of the article pays much attention to these peculiarities.
Keywords: Psychologist; society; spirituality professional; ethics; treatment; psychological climate; group; person; will; responsibility